Status and Management of Wildlife in Tripura - Gupta, A. K. (Indian Forester, 1998)
Tripura is smallest of the seven North-Eastern States, but because of her unique Bio-geographical and Zoo-geographical position, is very rich in bio-diversity and biological resources. Over the past few decades, however, various factors have adversely contributed towards wildlife conservation and management in the State. The paper records some of the unique faunal components of wildlife in the State and discusses about likely steps for sustainable wildlife conservation vis-a-vis meeting varied needs from diverse user groups.